Guide de la CNUDCI : L’essentiel sur la Commission des Nations Unies pour le droit commercial international - Commission des Nations Unies pour le Droit Commercial International (Secrétariat de la CNUDCI, 2013)

Applicable law in investor-state arbitration: the interplay between national and international law - Elisabeth Kjos, Hege (Oxford University Press, 2013)
This book examines the law, national and/or international, that arbitral tribunals apply on the merits to settle disputes between foreign investors and host states. In light of the freedom that the disputing parties and the arbitrators have when designating the applicable law, and because of the hybrid nature of legal relationship between investors and states, there is significant interplay between the national and the international legal order in investor-state arbitration. The book contains a comprehensive analysis of the relevant jurisprudence, legal instruments, and scholarship surrounding arbitral practice with respect to the application of national law and international law. It investigates the awards in which tribunals referred to consistency between the legal orders, and suggests alternatives to the traditional doctrines of monism and dualism to explain the relationship between the national and the international legal order. The book also addresses the territorialized or internationalized nature of the tribunals; relevant choice-of-law rules and methodologies; and the scope of the arbitration agreement, including the possibility of host states presenting counterclaims in investment treaty arbitration. Ultimately, it argues that in investor–state arbitration, national and international law do not only coexist but may be applied simultaneously; they are also interdependent, each complementing and informing the other both indirectly and directly for a larger common good: enforcement of rights and obligations regardless of their national or international origin.
https://ora.ox.ac.uk/objects/uuid:a52424f2-4c14-4cc1-a452-6d926a0a02fe https://library.oapen.org/bitstream/handle/20.500.12657/33860/453473.pdf
Keywords: Arbitral tribunals; Choice-of-law rules; Foreign investors; Host states; International law; Investor-state arbitration; National law; OAPEN

The Legal Effects of EU Agreements - Mendez, Mario (Oxford University Press, 2013)
Examining the legal effects of EU concluded treaties, this book provides an analysis of this increasingly important and rapidly growing area of EU law. The EU has concluded more than 1,000 treaties including recently its first human rights treaty (the UN Rights of Persons with Disability Convention). These agreements are regularly invoked in litigation in the Courts of the member states and before the EU courts in Luxembourg but their ramifications for the EU legal order and that of the member states remains underexplored. Through analysis of over 300 cases, the book finds evidence of a twin-track approach whereby the Court of Justice of the European Union (CJEU) adopts a maximalist approach to Treaty enforcement, where EU agreements are invoked in challenges to member state level action whilst largely insulating EU action from meaningful review vis-à-vis agreements. The book also reveals novel findings regarding the use of EU agreements in EU level litigation including: the types and which specific EU agreements (including the types of provisions) have arisen in litigation; the nature of the proceedings (preliminary rulings or direct actions) and the number of occasions in which they have been addressed in challenges to member state or EU action and the outcomes; who has been litigating (individuals, institutions, or member states) and which domestic courts have been referring questions to the CJEU. The significance of the judicial developments in this area are situated within the context of the domestic constitutional ramifications for member state legal orders thus revealing a neglected dimension in the constitutionalization debates, which traditionally emphasized the ramifications of internal EU law for the domestic constitutional order without expressly accommodating the constitutional significance of this external category of EU law nor the different challenges that this poses domestically.
Accepted: 2013-12-31 23:55:55
Keywords: Constitutionalization; Creative Commons; Cultural and strategic groupings; Direct effect of European Union law; Domestic courts; EU courts; EU law; EU level litigation; EUconcluded treaties; European Court of Justice; European Union; European Union law; GATT; General Agreement on Tariffs and Trade; International law; Treaty enforcement; WTO; World Trade Organization